Ammonium-nitrate mixtures dominated by NH4+-N promote the growth of pecan (Carya illinoinensis) through enhanced N uptake and assimilation - Chen, Mengyun; Zhu, Kaikai; Xie, Junyi; Liu, Junping; Qiao, Zhenbing; Tan, Pengpeng; Peng, Fangren (Frontiers in Plant Science, 2023)
Nitrogen (N) limits plant productivity, and its uptake and assimilation may be regulated by N sources, N assimilating enzymes, and N assimilation genes. Mastering the regulatory mechanisms of N uptake and assimilation is a key way to improve plant nitrogen use efficiency (NUE). However, it is poorly known how these factors interact to influence the growth process of pecans. In this study, the growth, nutrient uptake and N assimilation characteristics of pecan were analyzed by aeroponic cultivation at varying NH4+/NO3− ratios (0/0, 0/100,25/75, 50/50, 75/25,100/0 as CK, T1, T2, T3, T4, and T5). The results showed that T4 and T5 treatments optimally promoted the growth, nutrient uptake and N assimilating enzyme activities of pecan, which significantly increased aboveground biomass, average relative growth rate (RGR), root area, root activity, free amino acid (FAA) and total organic carbon (TOC) concentrations, nitrate reductase (NR), nitrite reductase (NiR), glutamine synthetase (GS), glutamate synthase (Fd-GOGAT and NADH-GOGAT), and glutamate dehydrogenase (GDH) activities. According to the qRT-PCR results, most of the N assimilation genes were expressed at higher levels in leaves and were mainly significantly up-regulated under T1 and T4 treatments. Correlation analysis showed that a correlation between N assimilating enzymes and N assimilating genes did not necessarily exist. The results of partial least squares path model (PLS-PM) analysis indicated that N assimilation genes could affect the growth of pecan by regulating N assimilation enzymes and nutrients. In summary, we suggested that the NH4+/NO3− ratio of 75:25 was more beneficial to improve the growth and NUE of pecan. The study provides a basis for further identification of the functions of N assimilation genes in the N assimilation process of pecan, and also provides a theoretical support for improving the yield of pecan by improving NUE, and promoting the scale development of pecan.